Investigating the Association between Travel History outside of Saudi Arabia and the Severity of COVID-19 cases: A Rerospective Study - Abdulsalam Mohammed Aleid; Waad Rabeh Aloufi; Saud Nayef Salem Aldanyowi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic has greatly impacted public health systems globally. Understanding risk factors associated with disease severity is important for developing appropriate treatment and prevention strategies. Pervious studies have suggested that international travel may contribute to the spread and severity of COVID-19.This study aimed to investigate whether a history of international travel is associated with increased severity of COVID-19 cases in Saudi Arabia. Methods: This was a retrospective cohort study conducted at tertiary care hospitals in Saudi Arabia between September- December 2020. Medical records of COVID-19 patients admitted during this period were reviewed. The primary exposure was a documented history of travel outside Saudi Arabia within the previous 14 days. The primary outcomes were ICU admission, length of ICU stay, and mortality. Demographic and clinical characteristics were also collected. Bivariate analyses using chi-square tests were conducted to assess associations between between travel history and outcomes. Efforts were made to control for potential confounders in the analysis. Results: A total of 1491 COVID-19 cases were included. 1036 (69.5%) reported a history of international travel, while 333 (22.3%) did not travel and the travel status was unknown for 114 (7.6%) cases. Cases with a travel history had significantly higher rates of ICU admission (21.2% vs 12.9%, p<0.001), longer mean ICU length of stay (9.5 vs 6.3 days, p=0.002), and higher mortality (5.9% vs 2.4%, p=0.002) compared to those without travel. Conclusion: Patients with COVID-19 who had recently traveled internationally had a more severe case of the disease, as shown by higher rates of intensive care unit admissions and mortality, as compared to those who had not traveled recently. Reducing the importation and severity of diseases could be achieved through travel screening and quarantine measures. Causal inferences are nevertheless constrained by the retrospective design. Validating these results and gaining a deeper understanding of the ways in which travel affects COVID-19 outcomes and epidemiology will require more prospective research.